Semantic modelling of self-realization of the personality - Dyakov, Sergey (Anales de Psicología / Annals of Psychology, 2022)
Introduction. The research is focused on studying self-organization of the personality in aspect of subjectness. The technique of modeling of social and role identification of the personality is presented. The research objective - to define semantic constructs self-updating in modeling of personal identification. Methods and techniques.- Semantic approach in structuring dichotomizing couples of constructs of personal identification is used. Offered original technique "Semantic Modelling of Self-organization of the Personality" ("SMSOP"). Respondents fill "Repertoire lattices" of J. Kelly. Results of sample are factorized. Respondents make modeling of in images "I am-real", "I am-ideal" and also images of "The Self-updated Personality" (SUP) and "Nonconformist" (NC), using a set of the linguistic constructs received by means of repertoire lattices of J. Kelly). The participants are 218 psychology students. Results and discussion. Comparative data of self-renewing constructs (in the aspect of "I-ideal") and the SUP and Oil Company models are shown. Although soup is a reference model of personality achievements (according to A. Maslow et al.), a NK reveals the properties of self-affirmation, In the semantics of mental self-organization (MSS) of a personality, respondents are not fully focused on these standards. The results of the factor analysis showed the peculiarities of the semantics of the students’ personality MCO in the aspect of self-renewal ("I-ideal"): emotional spontaneity and, at the same time, fortitude and self-confidence, as well as communication and well-being in life (associated with intelligence, ingenuity). Conclusions.- The semantics of self-renewing personalities is revealed to young people in positions that determine the possible, achievable aspects of the perspective of their life. The SUP and NC models are "perfect" for them.